2013
DOI: 10.1590/0004-282x20130168
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 may protect against progressing injury during the acute phase of ischemic stroke

Abstract: Atherosclerosis is an inflammatory disease, and ischemic stroke is one of its most common and devastating manifestations. Proinflammatory cytokines play a key role in the progression of the irreversible ischemic lesions. The presence of anti-inflammatory mediators may prevent secondary ischemic injury. Objectives: 1) To assess the relationship between stroke severity and the serum levels of IL-1β, IL-2, and IL-10; and 2) To analyze the neurological outcome after 72 h of ischemic stroke onset and expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
(10 reference statements)
3
19
0
9
Order By: Relevance
“…As compared to those who die, IS patients who improve have been shown to have lower IL-10 at 24 h, but increased levels at 72 h and 144 h (79). In other studies, low IL-10 levels are associated with acute neurologic decline post-stroke (76, 77). Yet another small study found no correlation with IL-10 and other cytokines and IS patient prognosis (86).…”
Section: Ischemic Strokementioning
confidence: 68%
“…As compared to those who die, IS patients who improve have been shown to have lower IL-10 at 24 h, but increased levels at 72 h and 144 h (79). In other studies, low IL-10 levels are associated with acute neurologic decline post-stroke (76, 77). Yet another small study found no correlation with IL-10 and other cytokines and IS patient prognosis (86).…”
Section: Ischemic Strokementioning
confidence: 68%
“…In this study, patients with lower IL-10 levels deteriorated neurologically within the irst 72 h. Thus, IL-10 may be involved in protective mechanisms during the acute phase of AIS [181]. However, IL-10's role in AIS and post-stroke recovery may be inluenced by additional patient characteristics, such as sex.…”
Section: Anti-inlammatory Il-10 In Aismentioning
confidence: 59%
“…Previous clinical studies have established a positive association between higher IL-10 levels during the acute phase and good outcome in IS [25,[31][32][33][34][35]. Nevertheless, no studies had previously investigated the role of IL-10 as a possible action mechanism of Treg-cells in acute phase of IS in humans.…”
Section: Discussionmentioning
confidence: 99%